Reducing binge drinking? The effect of a ban on late-night off-premise alcohol sales on alcohol-related hospital stays in Germany - Jan Marcus; Thomas Siedler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Excessive alcohol consumption among youth and young adults is a major public health concern. On March 1, 2010 the German federal state of Baden-W rttemberg banned the sale of alcoholic beverages between 10pm and 5am in off-premise outlets (e.g. kiosks, petrol stations, supermarkets). We use rich monthly administrative data from a 70 percent random sample of all hospitalizations for the years 2007-2010 in Germany in order to evaluate the impact of this policy on alcohol-related hospitalizations. Applying a difference-in-difference approach, we find that the policy change reduces alcohol-related hospitalizations among adolescents and young adults by about 9 percent. The empirical results suggest that limiting late hours during which alcoholic beverages are allowed to be sold is an effective and rather "costless" public health initiative for reducing high-risk drinking among youth and young adults.
Keywords: I12; I18; D04; 330